Chemical Constituents With Antiproliferative Activity From Pogostemon cablin (Blanco) Benth. - Peng, Xingjia; Ang, Song; Zhang, Yizi; Fan, Fenling; Wu, Mengshuo; Liang, Peiting; Wen, Yan; Gan, Lishe; Zhang, Kun; Li, Dongli; Yue, Jianmin (Frontiers in Chemistry, 2022)
Two new patchoulene sesquiterpenoid glycosides (1–2), a natural patchoulane-type sesquiterpenoid (3) and a natural cadinene-type sesquiterpenoid (4), were isolated from the aerial parts of Pogostemon cablin (Blanco) Benth., together with eleven known sesquiterpenoids (5–15) and eleven known flavonoids (16–26). Their chemical structures were elucidated on the basis of spectroscopic methods, including NMR, HRESIMS, IR, and CD spectroscopic data analysis, as well as chemical hydrolysis. The isolated compounds 1–13 and 15–26 were tested for inhibitory effects on the proliferation of HepG2 cancer cells. Among them, compounds 17 and 19 displayed anti-proliferative effects against HepG2 cells with IC50 values of 25.59 and 2.30 μM, respectively. Furthermore, the flow cytometry analysis and Western blotting assays revealed that compound 19 significantly induced apoptosis of HepG2 cells by downregulating the ratio of Bcl-2/Bax and upregulating the expression of cleaved caspase-3 and cleaved caspase-9. Therefore, the potential pharmaceutical applications of P. cablin would be applied according to our study findings.